2015
DOI: 10.1038/labinvest.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

miR-101a and miR-30b contribute to inflammatory cytokine-mediated β-cell dysfunction

Abstract: Inflammatory cytokines have a critical role in the progressive deterioration of pancreatic β-cell function and development of type 1 diabetes. Prolonged exposure of β-cells to inflammatory cytokines results in gene expression modifications, leading to loss of β-cell function. MicroRNAs (miRNAs) are small non-coding RNAs acting as key regulators of gene expression. Here, we demonstrate that miR-101a and miR-30b are key players in cytokine-mediated β-cell dysfunction. We found that IL-1β induces an increase in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 35 publications
5
53
0
1
Order By: Relevance
“…For example, Belgard et al show that overexpression of the miR-200 family in mice is sufficient to induce β-cell apoptosis and lethal T2DM through indirect activation of the pro-apoptotic genes Trp53 and Bax [12], while elevated miR-34a promotes MIN6 cell apoptosis by directly binding to the 3’-UTR of the anti-apoptotic gene Bcl-2 [13]. …”
Section: Mirnas and Pancreatic β-Cellsmentioning
confidence: 99%
“…For example, Belgard et al show that overexpression of the miR-200 family in mice is sufficient to induce β-cell apoptosis and lethal T2DM through indirect activation of the pro-apoptotic genes Trp53 and Bax [12], while elevated miR-34a promotes MIN6 cell apoptosis by directly binding to the 3’-UTR of the anti-apoptotic gene Bcl-2 [13]. …”
Section: Mirnas and Pancreatic β-Cellsmentioning
confidence: 99%
“…Several recent studies have indicated a role for miRNAs in the regulation of autoimmunity progression and diabetes development (2023), including the regulation of inflammatory cytokine-mediated β-cell dysfunction and death (2426). Additionally, there may be a link between miRNAs and regulation of T1D candidate genes (27) and β-cell responses to viral infection (28).…”
Section: Introductionmentioning
confidence: 99%
“…97 In our previous study, we found that IL-1β treatment induced increased miR-101a and miR-30b expression in β-cells and that the two miRNAs contributed to cytokinemediated β-cell apoptosis and dysfunction. 98 miR-101a and miR-30b downregulate proinsulin expression and reduce the insulin content via direct suppression of the transcriptional factor Neurod1. Furthermore, miR-101a/miR-30b-mediated β-cell apoptosis is related to decreased Bcl2 expression.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%
“…We also showed that miR-101a impaired GSIS by inhibiting Onecut2. 98 Recently, Grieco et al reported that miR-23a, miR-23b and miR-149 were downregulated upon exposure of β-cells to the proinflammatory cytokines IL-1β+IFN-γ. These downregulated miRNAs were further demonstrated to modulate the expression levels of the pro-apoptotic Bh3-only proteins Dp5 and Puma, consequently affecting β-cell apoptosis.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%
See 1 more Smart Citation